1994
DOI: 10.1016/0303-7207(94)90112-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antiandrogen action: Conformational changes of the receptor

Abstract: Androgen receptor mRNA was translated in vitro, and androgen-and antiandrogen-bound receptor complexes were studied using limited proteotytic digestion by trypsin. Partial proteolysis of androgen-Lund receptor proteiu resulted in a 29-kDa proteolysis-resisting fragment, whereas antiandrogen binding stabilised a 3%kDa fragment. Both fragments contain the entire ligand binding domain, and the 35kDa fragment extended into the hinge region of the receptor. Several antiandrogens show agonistic properties for a muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
4
37
0
1
Order By: Relevance
“…As expected, BIC-occupied AR remained unaffected by the T877A mutation, and showed no change in response to N-CoR. This is in accordance with the previous finding that the BIC-induced AR conformation is not changed by the T877A mutation [9], and with the ability of T877A-AR from LNCaP cells to recruit N-CoR to the PSA promoter [25] and subsequently inhibit PSA production in the presence of BIC [43].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, BIC-occupied AR remained unaffected by the T877A mutation, and showed no change in response to N-CoR. This is in accordance with the previous finding that the BIC-induced AR conformation is not changed by the T877A mutation [9], and with the ability of T877A-AR from LNCaP cells to recruit N-CoR to the PSA promoter [25] and subsequently inhibit PSA production in the presence of BIC [43].…”
Section: Discussionsupporting
confidence: 92%
“…The underlying molecular mechanism for the change in response to OHF and CPA is not fully understood. Some clue is given by the observation that, after binding of OHF and CPA, the T877A mutation allows the AR to adopt an active conformation, similar to that found with the agonists R1881 and DHT [9,17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Functional characterization showed that the mutant receptor induced transcription upon addition of RU486 (14). These results led to the hypothesis that the activity of antagonists is based on the induction of a non-functional conformation at the C terminus of steroid hormone receptors (4 -6, 11).Androgen binding to the androgen receptor (AR) 1 changed the receptor structure in such a way that the entire ligand binding domain resisted proteolytic degradation (10,16,17). However, for the antiandrogen-bound receptor, the outcome of preliminary studies on resistance against proteolytic degradation varied in different investigations.…”
mentioning
confidence: 99%
“…Androgen binding to the androgen receptor (AR) 1 changed the receptor structure in such a way that the entire ligand binding domain resisted proteolytic degradation (10,16,17). However, for the antiandrogen-bound receptor, the outcome of preliminary studies on resistance against proteolytic degradation varied in different investigations.…”
mentioning
confidence: 99%